Micro- and nanoplastic induced cellular toxicity in mammals: A review - Banerjee, Amrita; Shelver, Weilin L. (The Science of the total environment, 2021)
Plastic based products are ubiquitous due to their tremendous utility in our daily lives. However, the limited biodegradable nature of plastics has recently raised pollution concerns globally, especially micro- and nanoplastics. These anthropogenic pollutants are either manufactured specifically in the small size range for various commercial applications or formed due to fragmentation of macro plastics in the environment. Micro- and nanoplastics are currently widespread in the oceans, freshwater bodies, land and even present in our food. The biological effects of micro- and nanoplastics on aquatic organisms are well documented but their impacts on mammalian system have not been rigorously investigated. This review discusses the potential routes of exposure to micro- and nanoplastics, biological effects of these particles in mammalian cells, factors influencing toxicity, and the probable mechanisms of cytotoxicity. In general, small size, positive charge, high dose, and presence of toxic additives or pollutants in the micro/nanoplastics appear to induce cellular toxicity through oxidative stress, membrane damage, immune response and genotoxicity. Understanding the cellular fate and toxicity of these materials may help extrapolate risks to mammals. [Display omitted] •Impact of micro- and nanoplastics on human health is not known.•Human/mammalian cell-based toxicity studies may provide insights on health impact.•Cytotoxicity of micro/nanoplastics varies with cell type.•Particle size, dose, charge, exposure time, type and additives dictate effects.•Oxidative stress and membrane damage are two main causes of cell deaths.